2008 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--4187
|View full text |Cite
|
Sign up to set email alerts
|

Imelt: Integrating Mathematics, Engineering, And Literacy In The Teaching Of Mathematics

Abstract: up with area school teachers from under-performing schools to develop engaging projects. These projects utilize techniques that have proven successful in Integrated Engineering and Science Curricula in the college. These techniques include team building, collaborative learning, and hands-on activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…STEM education has become increasingly central to U.S. economic competitiveness and growth. Long-term strategies to maintain and increase living standards and promote opportunity will require unprecedented coordinated efforts among public, private, and non-profit entities to promote innovation and to prepare an adequate supply of qualified STEM workers that are capable of translating knowledge and skills into new processes, products, and services [2][3][4][5][6] .…”
Section: Problem Definitionmentioning
confidence: 99%
“…STEM education has become increasingly central to U.S. economic competitiveness and growth. Long-term strategies to maintain and increase living standards and promote opportunity will require unprecedented coordinated efforts among public, private, and non-profit entities to promote innovation and to prepare an adequate supply of qualified STEM workers that are capable of translating knowledge and skills into new processes, products, and services [2][3][4][5][6] .…”
Section: Problem Definitionmentioning
confidence: 99%
“…NASA-Threads provides school systems with a rigorous program that showcases a systems-level understanding of real-world applications of mathematics, science, and engineering. Our previous experience has shown that long-term impact on K12 students comes through close collaborative relationships between teachers and university faculty [4][5][6][7][8] . NASA-Threads provides a hands-on, context-based approach to math and science professional development in preparing teachers to become the educators of the future.…”
Section: Project Descriptionmentioning
confidence: 99%
“…Science, Technology, Engineering, and Mathematics (STEM) education has become increasingly central to national economic competitiveness and growth in almost every developing and developed country. Long-term strategies to maintain and increase living standards and promote opportunity will require unprecedented coordinated efforts among public, private, and non-profit entities to promote research and innovation and to prepare an adequate supply of qualified STEM workers that are capable of translating knowledge and skills into new processes, products, and services [11][12]. Specialization in STEM fields differs among countries, with the United States, European Union countries, and Japan focusing more in health sciences, while China and India specialize more in engineering and technology as measured by journal articles and conference papers [12].…”
Section: Mrrt Project Impact To Stem Recruitment Effortsmentioning
confidence: 99%